THE MEANING OF THE PHILOSOPHY WISE (KINAA),BRAVE (BARANI), AND SMART (MANARANG) AS ONE OF THE LOCAL WISDOM OF TORAJA - Tadius Tadius; Benyamin Salu (Universitas Muhammadiyah Makassar, 2021)
Philosophy is defined as the most basic assumptions, ideas and attitudes possessed by a person or society; views of life; (KBBI online). The local philosophy is more identical to the most basic inner attitudes possessed by a person or society. Along with the development of human civilization, science is increasingly advanced. The advancement of science and technology has had a significant impact on the almost fading of local culture and wisdom in society. The purpose of this research is to deeply analyze the meaning of the philosophy of